Utilisation d'Internet et relations sociales - Simon Laflamme; Sylvie Lafortune (Communication)
The debate over the impact of the Internet has been going on for well over a decade. On the one hand, pessimists maintain that the Internet separates people from one another as they withdraw in a virtual world. On the other hand, optimists argue that the Net removes physical barriers and provides countless possibilities to communicate and meet people. This study does not attempt to confirm or disprove either one of these opposing views. Rather, its objective is to determine if there is a link between Internet use and interpersonal relationships. In particular, it examines whether increased use of the Internet leads to isolation or, alternatively, more numerous, frequent and intense communications.